EVALUATION OF THE QUALITY ASSURANCE SYSTEM FOR THE BACHELOR OF SPORTS COACHING EDUCATION PROGRAM (FKIP) AT GUNUNG LEUSER UNIVERSITY, SOUTHEAST ACEH REGENCY - Zulyadin Berutu (Jurnal Penelitian Progresif, 2026)
Internal Quality Assurance Systems (SPMI) are not yet a priority for most universities when compared to External Quality Assurance Systems (SPME). Law No. 12 of 2012 on Higher Education states that SPMI and SPME are part of a system. It is suspected that SPMI by several universities does not have a significant impact like SPME, where universities will receive accreditation results. This research was conducted in February 2026. The purpose of this research is to evaluate the SPMI program developed by the Sports Coaching Education Program (FKIP) at Gunung Leuser University in Southeast Aceh Regency. C. The assessment method was carried out using a system approach that included aspects of context, input, process, and output, with reference to relevant research literature. The implementation of SPMI in the Sports Coaching Education program (FKIP) at Gunung Leuser University in Southeast Aceh Regency has been running well, when compared to PPEPP in all aspects of its implementation stages. The SPMI evaluation recommendations in this study are addressed to three stakeholders, namely the Directorate of Quality Assurance, the University-level Quality Assurance Agency, and the Head of the Sports Coaching Education Study Program (FKIP) at Gunung Leuser University, Southeast Aceh Regency.